Apprentissage et tabellionage à Rouen (1360-1421) : qu’enregistrent les contrats écrits ? - François Rivière (Tabularia)
In Rouen, the apprenticeship contracts seem to be scarce in the registers of the notaries (tabellion), because of archival losses after 1421. However, the frequency of their registration suffices to gather a corpus as significant as in other cities. Nonetheless, the comparison with the archives of the commune of Rouen and of the plumbers-pewterers suggests that ordinary apprenticeship contracts were not written down and registered. The study of the form of the contracts separates the stereotyped phrases from the singular motives that led to draw up a notarial deed. Independently from craft guilds, the parties, especially orphans or adult apprentices, resorted to written agreements to make sure that their obligations were reciprocal or that financially substantial and/or long term commitments were honoured.